2011
DOI: 10.7863/jum.2011.30.4.547
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of the Ultrasonographic Criteria for Diagnosing Lymph Node Metastasis in Patients With Cutaneous Melanoma

Abstract: The purpose of this systematic review of the literature was to evaluate the use of ultrasonography (US) in the assessment of lymph node metastasis in patients with cutaneous melanoma. A multimodal strategy was used, which was mainly based on a PubMed database search. Among the 201 cumulative articles collected (years 1989-2009), 31 were found to match all of the inclusion criteria and to provide a description of the use of US scanning in lymph node melanoma metastasis. Data extracted included the author's name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 55 publications
0
29
0
1
Order By: Relevance
“…-To evaluate retrospectively the morphological aspects of some skin growths at ultrasound B-mode and colorpower Doppler using a high-frequency transducer [5][6][7][8][9][10][11][12][13][14][15][16][17]; to correlate the results of ultrasound with dermoscopy examination and histological data to identify specific ultrasound patterns to differentiate benign from malignant lesions. -To select melanomas among the malignant lesions, to describe their sonographic pattern, the presence and morphology of vascular signal and to compare their thickness at US with the histological Breslow index and check whether or not our data were combined with data already present in the literature.…”
Section: Aimsmentioning
confidence: 99%
See 1 more Smart Citation
“…-To evaluate retrospectively the morphological aspects of some skin growths at ultrasound B-mode and colorpower Doppler using a high-frequency transducer [5][6][7][8][9][10][11][12][13][14][15][16][17]; to correlate the results of ultrasound with dermoscopy examination and histological data to identify specific ultrasound patterns to differentiate benign from malignant lesions. -To select melanomas among the malignant lesions, to describe their sonographic pattern, the presence and morphology of vascular signal and to compare their thickness at US with the histological Breslow index and check whether or not our data were combined with data already present in the literature.…”
Section: Aimsmentioning
confidence: 99%
“…The aim of this study was -To evaluate retrospectively the characteristics of normal skin by ultrasound examinations performed with a high-frequency transducer [5][6][7][8][9][10][11][12][13][14][15][16][17].…”
Section: Aimsmentioning
confidence: 99%
“…Signs of malignant lymph nodes are considered to be the hypoechoic and heterogeneous texture, the round shape, the lack of hyperechoic hilum, the ill-defined margins, and the peripheral or mixed pattern of vascularization [4,5]. Until now no absolute criterion has been defined due to the false positive and false negative aspects encountered in normal and pathological lymph nodes [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2011 meta-analysis, Catalano et al [8] found that 31 out of 201 articles matched their inclusion criteria to provide a description of the use of US scanning for the detection of melanoma lymph node metastases. This compilation of articles showed that, in contrast to older systems, modern high-resolution scanners now allow for recognition of very subtle abnormalities within the lymph node.…”
Section: Introductionmentioning
confidence: 98%
“…Even if set adequately for detecting slow flow, the scanners used in the past would frequently not have been able to allow for the recognition of relevant signals in malignant lymph nodes, simply because of the low intrinsic sensitivity of those machines [8]. Instead, modern equipment would be very sensitive to slow flow and optimal depiction of the abnormal angiographic architecture of superficial lymph node metastases [8].…”
Section: Introductionmentioning
confidence: 98%